Dichondra repens J.R.Forst. and G.Forst.: A Review of Its Traditional Uses, Chemistry, Pharmacology, Toxicology and Applications - Yao, Qi; Wang, Ying; Dong, Zhiyu; Lai, Chencen; Chang, Botao; Gong, Qiuju; Ren, Shuaijun; Sun, Dongxue; Lu, Jie; Gao, Ying (Frontiers in Pharmacology, 2021)
Ethnopharmacology relevance: Dichondra repens Forst. (DRF; Convolvulaceae, called Matijin in Chinese), has been traditionally used to treat jaundice, bacillary dysentery, urinary tract infection, edema, contusions, and strains and sprains based on traditional Chinese medicine (TCM) concepts. Aim of study: This paper intends to provide a comprehensive and critical analysis on research of DRF and focusing on a relationship between traditional uses and pharmacological effects, evaluating the therapeutic potential of this plant. Methods: Relevant data on DRF were retrieved from available databases and a hand-research by screening the keywords including “Dichondra repens Forst.”, “chemistry”, “pharmacology”, “toxicity”, and “applications”. Results: The heat-clearing and detoxifying, and removing the phlegm and turbid urine effects of DRF are linked to its anti-hepatitis B virus (HBV), anti-inflammatory, and hepatoprotective activities. Especially, the hepatoprotective effects of DRF are mainly based on anti-HBV activities of phenylalanine dipeptides Matijin-Su (MTS) and its derivatives derived from this plant. Further, a phase I anti-HBV clinical trial of a candidate compound named bentysrepinine (Y101, Chinese name Tifentai) has been completed. Also, anti-tumor, analgesic, and antibacterial properties have been reported in the extracts and compounds from DRF. Although pharmacy, pharmacodynamics, toxicology, and pharmacokinetics of bentysrepinine have been systemically reported, it is encouraged to evaluate other active compounds systemically in preclinic. Additionally, it is still rare for action mechanisms of extracts or compounds from this plant. Conclusions: Although the systemic studies on bentysrepinine provide good references for future research and development of DRF, it is still necessary to evaluate safety, chemistry, pharmacology of the extracts or compounds from DRF regarding the link between traditional uses and modern applications before the future clinical trials. In addition, strict quality control measures are needed to investigate the pharmacology and clinical applications of this plant. Except HBV-related diseases, bacterial sepsis, cholecystitis and tumors may be prior therapeutic scopes of this plant in the future.